Does Death of a Family Member Moderate the Relationship between Religious Attendance and Depressive Symptoms? The HUNT Study, Norway. (13th May 2012) - Sørensen, Torgeir; Danbolt, Lars J.; Holmen, Jostein; Koenig, Harold G.; Lien, Lars
Abstract : Background . The death of a family member is a stressful life event and can result in an increased level of depressive symptoms. Previous American research has shown inverse relationships between religious involvement and depression. European investigations are few and findings inconsistent; different contexts may have an important influence on findings. We therefore investigated the relationship between attendance at church/prayer house and depressive symptoms, and whether this relationship was moderated by the death of a close family member, in Norway. Methods . A population-based sample from the Nord-Trøndelag Health Study, Norway (HUNT 3, N = 37, 981), was the population examined. Multiple regression and interaction tests were utilised. Results . Religious attendees had lower scores on depressive symptoms than non-attendees; death of a close family member moderated this relationship. The inverse relationships between attendance at church/prayer house and depressive symptoms were greater among those experiencing the death of an immediate family member in the last twelve months compared to those without such an experience, with men's decrease of depressive symptoms more pronounced than women's. Conclusion . In a population-based study in Norway, attendance at church/prayer house was associated with lower depressive symptoms, and the death of a close relative and gender moderated this relationship.